Middle frame processing method, middle frame and electronic device - LIU XIN; QI XIAOXIANG; LIN JUNHAO; CHEN SHUIQIN (2021)
The embodiment of the invention provides a middle frame processing method, a middle frame and an electronic device. The middle frame processing method comprises: a middle frame body comprising an inner surface and an outer surface which are opposite to each other, the middle frame body being a transparent middle frame body, the outer surface being provided with a preset carving area, a coating being formed on the outer surface, and the coating covering the outer surface including the preset carving area; removing the coating at the preset engraving area; forming an optical layer on the diaphragm body to obtain a diaphragm, and the diaphragm body being a transparent diaphragm body; and attaching the diaphragm to the inner surface to obtain the middle frame. In the embodiment of the invention, the coating on the outer surface of the middle frame body is removed, and then the diaphragm is attached to the inner surface of the middle frame body, so that the middle frame shows a color effectthrough the coating and